Between national and local: Identity representations of post-colonial Hong Kong in a local English newspaper. (August 2020) - Liu, Ming; Zhong, Jiali
Abstract: This study gives a corpus-assisted discourse study of the representations of Hong Kong identity with identity labels in a Hong Kong English newspaper (i.e., the South China Morning Post ) in the last two decades. It not only identifies the various labels used for the concerned parties, but also examines their varied use in the changing social political context and the ideologies behind the choice of some prominent identity labels. The finding suggests that the newspaper prefers to choose labels that foreground the local identity of Hong Kong rather than its national identification. This trend has become particularly evident since 2003 and the constructions of Hong Kong identity have become increasingly negative in the last few years.